(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
the article discusses a new approach to the content, technology, methods and methodology of educating schoolchildren on the basis of national values, shows the theoretical and practical foundations of education aimed at forming a high value of the individual.